\(8\left(x-\frac{1}{2}\right)\left(x^2+\frac{1}{2}x+\frac{1}{4}\right)-4x\left(1-x+2x^2\right)+2=0\)
\(\Leftrightarrow8\left[x^3-\left(\frac{1}{2}\right)^3\right]-4x+4x^2-8x^3+2=0\)
\(\Leftrightarrow8x^3-1-4x+4x^2-8x^3+2=0\)
\(\Leftrightarrow4x^2-4x+1=0\Leftrightarrow\left(2x-1\right)^2=0\)
\(\Leftrightarrow x=\frac{1}{2}\)
8(x-1/2)(x^2+1/2x+1/4) - 4x(1-x+2x^2)+2=0
=> 8𝑥^3 − 1 − 8𝑥^3 + 4𝑥2 − 4𝑥 + 2 = 0
=> 4𝑥2 − 4𝑥 + 1 = 0
=> ( 2x - 1 )^2 = 0
=> 2x - 1 = 0
=> 2x = 1
=> x = 1/2
<=> 8( x3 - 1/8 ) - 4x + 4x2 - 8x3 + 2 = 0
<=> 8x3 - 1 - 4x + 4x2 - 8x3 + 2 = 0
<=> 4x2 - 4x + 1 = 0
<=> ( 2x - 1 )2 = 0 <=> x = 1/2
Trả lời:
\(8\left(x-\frac{1}{2}\right)\left(x^2+\frac{1}{2}x+\frac{1}{4}\right)-4x\left(1-x+2x^2\right)+2=0\)
\(\Leftrightarrow8\left(x^3-\frac{1}{8}\right)-4x+4x^2-8x^3+2=0\)
\(\Leftrightarrow8x^3-1-4x+4x^2-8x^3+2=0\)
\(\Leftrightarrow4x^2-4x+1=0\)
\(\Leftrightarrow\left(2x-1\right)^2=0\)
\(\Leftrightarrow2x-1=0\)
\(\Leftrightarrow x=\frac{1}{2}\)
Vậy x = 1/2 là nghiệm của pt.